Selective Deprotection of N-Tosyl Alkoxyamines Using Bistrifluoromethane Sulfonimide: Formation of Oxime Ethers - Azizi, Mohamed Salah; Cossy, Janine (Synlett, 2018)
The detosylation of N-tosyl alkoxyamines was realized by treatment with benzaldehyde and bistrifluoromethane sulfonimide as the catalyst to afford the corresponding oxime ethers. The reaction is chemoselective as N-tosyl amines are not deprotected. A mechanism is proposed for this deprotection.
Keywords: N-detosylation; bistrifluoromethane sulfonimide; N-tosyl-alkoxyamine; benzaldehyde; oxime ethers